Pengaruh Kepemimpinan Transformasional Terhadap Turnover Intention dan Organizational Citizenship Behavior (OCB): Peran Media si Pemberdayaan Psikologis dan Komitmen Afektif (Studi PadaWs Warung Steak di Karesidenan Surakarta) - Mega Wandani; Sinto Sunaryo (Universitas Kristen Indonesia Toraja, 2022)
This study aims to exam ine the effect of transformational leadership on turn over intention and OCB by considering the role of psychological empowerment and affective commitment. Conducted at WS Warung Steak, this study involved 121 participants. For the analysis of this study using SEM-PLS w ith SmartPLS version 3.0. The finding of this study is that transformational leadership has a significant negative effect on turnover intention. Transformational leadership has a positive effect on employee OCB behavior. Transformational leadership has a significant positive effect on psychological empowerment. Transformational leadership has a significant positive effect on affective commitment. Psychological empowerment has a significant positive effecton employee OCB behavior. Psychological empowerment has a significant negative effect on turnover intention. Affective commitment has a positive and significant effect on OCB. OCB behavior of employees has a negative influence on turnover intention. Psychological empowerment mediates the relationship between transformational leadership on employee OCB. Psychological empowerment has been shown to mediate the effect of transformational leadership on turn over intention. Affective commitment mediates transformational leadership in OCB . Further research is recommended to develop further research on the relationship of transformational leadership to turnover intention and OCB by considering other variables in order to obtain more in -depth results.